The quiet revolution and emerging modern revolution in agri-food processing in Sub-Saharan Africa - Reardon, Thomas; Awosuke, Titus; Haggblade, Steven; Minten, Bart; Vos, Rob (Alliance for a Green Revolution in Africa, 2019)
Over the past two decades agricultural markets, trade, foreign direct investments, and food systems in Southern Africa have experienced dramatic transformation (Reardon et al., 2019; Tschirley, Dolislager, Reardon, & Snyder, 2015). Many of the region’s economies were characterized by periods of relatively fast economic growth (around 3% to 6%), increasing population and strong patterns of urbanization that have triggered a diversification in diets. Despite these strong trends, the current debates are to large extent still dominated by three key underlying themes, namely (1) yield worries; (2) import worries; and (3) export dreams. These underlying themes are also evident in most of the policy debates that have a strong producer-led bias. The careful assessment of key policy and investment requirements and the potential impacts of rapid growth in agricultural productivity on markets and supply chains, is generally less covered than farm level productivity. Even in the most recent national agricultural investment plans (NAIPS) developed by many African states, market and supply chain considerations are addressed under the general theme of public–private partnerships, without detailed analyses of recent trends in commodity markets and investment patterns by actors in the middle segments (wholesale, logistics, and processing) of the supply chains. Reardon (2015) calls these middle segments the “hidden middle”—they are not missing, rather, they are “hidden” from the debate—although their value is estimated at approximately 40% of the supply chain. Despite the overwhelming focus on farm level productivity, there has been a rapid evolution in supply chains in several markets, yields have increased and import worries have turned into rapid increases of net exports. In fact, in some markets the rapid increase in production has resulted in local gluts driving down local prices far below import parity levels and consequently eroding farm profits. Growth has already stagnated, hitting a wall of local surpluses with low margins and high transaction costs that at best allow for temporary forays into exports to neighbors who themselves are working up to local gluts. The main objective of this chapter is to follow a market-led approach that offers an alternative assessment of the most recent trends in agricultural markets and the behavior of midstream actors in these fast-changing food systems. The first section provides an overview of the evolution of Africa’s agricultural trade; the second highlights the key elements of hitting the wall in some of the African markets and the importance of venting surpluses; and the last section provides a taxonomy of wholesale/logistics-cum-supply chain services firms in Africa that fill the midstream. In many cases these actors can be classified as “midstream heroes” that have brought real capital and long-term investments to the table, and have been a major driving force for growth and off-farm employment in several African economies. Increases in productions arising from capital investments that have provided markets for primary farm output have also seen some of this production being exported, and thus, the venting off surpluses to reduce local glut.